ANALYSIS OF WEBSITE BASED LIBRARY INFORMATION SYSTEMS AT SMKN 8 BANDUNG - Nenden Aryani Goddess; Ari Purno Wahyu Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Every school should be able to develop students' interest in reading. One of them is by providing a library at school. Currently, there are still many school libraries whose management is still manual, such as starting from recording member data, bookkeeping data to storing other data related to transaction processing to making reports, so it is possible during the process there is an error in recording, lack of accurate reports and delay in finding the required data. Several methods of developing information systems consist of the Research and Development (R&D) method, which is a research method that aims to produce certain products and test the effectiveness of these products and the FAST method which is the best solution to solve the problems that exist in this library. The FAST method makes system design easier and on target. And with the existence of a website-based library information system at SMKN 8 Bandung, it increases students' reading interest because they can access it anywhere and anytime without being limited by time, making it easier for officers to manage library data.